Reginald Pecock on the Authority of Reason, Scripture and Tradition - Lahey, Stephen E. (The journal of ecclesiastical history, 2005)
Bishop Reginald Pecock (c. 1390–1461) is remembered for vernacular works formulated to combat Lollardy using reason, not the force of ecclesiastical authority. He argued that Scripture's teachings are true not because they are in Scripture, but because they are evident to unassisted reason. While scholars have explored his arguments in ecclesiastical and historical context, little analysis exists of the scholastic background to Pecock's conception of the relation of reason to faith. This article suggests that Pecock's arguments are grounded in the thought of Aquinas and Scotus, and illustrates how his understanding of reason's capabilities directs his conception of the authority of Scripture and church tradition.